Studi Komparasi Pendapatan Driver Gojek dan Maxim Terhadap Upah Minimum di Kota Surabaya - Nadzah, Savinathul; Agustin, Istiqomah; Prismadifa, Raharka; Ayu, Niken; Sholihatin, Endang (Economie: Jurnal Ilmu Ekonomi, 2022)
This research aims to determine the comparison of the amount of income between Gojek and Maxim drivers for one month, and to find out whether the income of Gojek and Maxim drivers has reached the Surabaya Minimum Wage or not. This research model uses case studies in the field with a quantitative descriptive method with data collection techniques through field interviews with 6 Gojek drivers and 6 Maxim drivers around UPN Veteran East Java, which was conducted for one week. From the results of the interviews, the researchers concluded that the average income of Gojek and Maxim drivers still did not meet the Surabaya City Minimum Wage, although there were several Gojek drivers whose income reached the City UMK.